Early Start Denver Model. Un modello Evidence Based per l’intervento educativo precoce nei Disturbi dello Spettro Autistico - Fontani, Saverio (Studi sulla Formazione/Open Journal of Education, 2016)
The Autism Spectrum Disorders represents one of the most complex developmental disabilities for the massive deficit of communication competences. The social disability related to disorders is the main objective of the intervention of the Early Start Denver Model – ESDM (Rogers & Dawson, 2010), which can be considered as one of the most advanced models for early educational intervention according the perspective of Evidence Based Education. In this paper the theoretical foundations of the model are presented and its implications for a modern inclusive education are discussed..